Anti-viral Effect of Bifidobacterium adolescentis against Noroviruses - Li, Dan; Breiman, Adrien; le Pendu, Jacques; Uyttendaele, Mieke (Frontiers in Microbiology, 2016)
This study aims to investigate the effect of Bifidobacterium adolescentis against noroviruses (NoVs). Murine norovirus-1 (MNV-1) used as a surrogate was detected by plaque assay and RT-qPCR. Human NoV virus like particles (VLPs) were detected by cell-binding assay. It was shown that the presence of B. adolescentis could inhibit the multiplication of MNV-1 on RAW 264.7 cells within 48h of co-incubation period at 37°C. This inhibition did not occur at the viral binding stage, as no difference was observed in MNV-1 genomic copies collected from washed RAW 264.7 cells without and with B. adolescentis after co-incubation for 1h at room temperature. Meanwhile, the presence of B. adolescentis decreased the binding of human NoV GI.1 VLPs to both Caco-2 cells and HT-29 cells, while no reduction was induced for the binding of human NoV GII.4 VLPs to Caco-2 cells.